Evaluation of Pressure Boundary Conditions for Permeability Calculations Using the Lattice-Boltzmann Method (Advances in Applied Mathematics and Mechanics, 2021)
Lattice-Boltzmann (LB) simulations are a common tool to numericallyestimate the permeability of porous media. For valuable results, theporous structure has to be well resolved resulting in a largecomputational effort as well as high memory demands. In order to estimatethe permeability of realistic samples, it is of importance to not onlyimplement very efficient codes, but also to choose the most appropriate simulation setup to achieve accurate results. With the focus on accuracyand computational effort, we present a comparison between differentmethods to apply an effective pressure gradient, efficient boundaryconditions, as well as two LB implementations based on pore-matrix andpore-list data structures.